Exhaust purification catalyst device
By combining zeolite particles and inorganic oxide particles in the catalyst coating layer and optimizing the particle size ratio and pore size structure, the problem of low NOx adsorption and release efficiency in the prior art is solved, the exhaust purification efficiency is improved, and the catalyst is enhanced purification capability.
Patent Information
- Application Number
- CN202180024594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2021-03-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-03-17
AI Technical Summary
The existing exhaust purification catalyst device is difficult to effectively adsorb and release NOx under low temperature conditions, and the adhesion and thickness uniformity of the catalyst coating layer are insufficient, which affects the purification efficiency.
在催化剂被覆层中结合沸石粒子和其他无机氧化物粒子,并通过调整粒径比和孔径结构,形成充分的排气流路以提高NOx和HC的吸附和释放效率,使用贵金属催化剂以增强净化能力。
Effective adsorption and high-temperature release of NOx and HC, especially NOx, is achieved, which improves the exhaust purification efficiency and avoids the adhesion and thickness unevenness of the catalyst coating.
Smart Images

Figure CN115335149B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an exhaust gas purification catalyst device. Background Art
[0002] In order to purify nitrogen oxides (NOx), hydrocarbons (HC), carbon monoxide (CO) and the like contained in exhaust gas discharged from an engine of an automobile or the like and release them into the atmosphere, an exhaust gas purification catalyst device having a catalyst coating layer formed on a cordierite honeycomb substrate is used.
[0003] Zeolite is known as a material used for a catalyst coating layer of an exhaust gas purification catalyst device. Zeolite is expected to have the function of adsorbing NOx and HC, especially NOx, at low temperatures and retaining it at high temperatures, and releasing NOx at high temperatures.
[0004] That is, under low temperature conditions such as immediately after the engine is started, when the exhaust temperature is low and the exhaust purification catalyst is difficult to activate and NOx catalytic purification is difficult to occur, the zeolite adsorbs and holds NOx, thereby reducing the NOx concentration in the exhaust gas. On the other hand, when the exhaust temperature rises to a high temperature that can activate the exhaust purification catalyst, NOx is released and used for catalytic purification.
[0005] Zeolite can improve the exhaust gas purification efficiency through this function.
[0006] However, it is known that when the catalyst coating layer is composed of, for example, zeolite alone, there may be problems such as insufficient adhesion between the honeycomb substrate and the catalyst coating layer and insufficient thickness uniformity of the catalyst coating layer. Therefore, an exhaust gas purification catalyst device is proposed in which an inorganic oxide other than zeolite is arranged in the catalyst coating layer together with zeolite.
[0007] For example, Patent Document 1 describes an exhaust gas purification catalyst in which a HC adsorbent layer and a purification catalyst component layer are sequentially stacked on a carrier, and the HC adsorbent layer contains zeolite and alumina containing a metal element.
[0008] Prior art literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-35130 Summary of the invention
[0010] In the conventional exhaust gas purification catalyst device, even when zeolite is contained in the catalyst coating layer, the functions of adsorbing, retaining and releasing NOx and HC, especially NOx, are not necessarily fully exerted.
[0011] The present invention has been made in view of the above circumstances. Therefore, an object of the present invention is to provide an exhaust gas purification catalyst device, which is an exhaust gas purification catalyst device including zeolite particles and other particles in a catalyst coating layer, and can effectively adsorb and release NOx and HC, especially NOx, and has a large adsorption amount of NOx.
[0012] The present invention is as follows.
[0013] [Scheme 1] An exhaust gas purification catalyst device comprises a substrate and a catalyst coating layer on the substrate,
[0014] The catalyst coating layer includes zeolite particles, inorganic oxide particles other than the zeolite particles, and a catalyst noble metal, and
[0015] The average particle size of the zeolite particles is ZEO The average particle size d of the inorganic oxide particles other than the zeolite particles OX The ratio d ZEO / d OX Below 3.4.
[0016] [Scheme 2] According to the exhaust gas purification catalyst device of scheme 1, the ratio d ZEO / d OX It is above 0.30.
[0017] <<Scheme 3>> In the exhaust gas purification catalyst device according to scheme 1 or 2, the catalytic noble metal is supported on the zeolite particles.
[0018] [Scheme 4] The exhaust gas purification catalyst device according to any one of schemes 1 to 3, wherein the catalytic noble metal is one or two selected from Pt and Pd.
[0019] [Scheme 5] According to any one of schemes 1 to 4, the inorganic oxide particles other than the zeolite particles are particles containing one or more selected from aluminum oxide, silicon oxide, titanium oxide, cerium oxide and zirconium oxide and rare earth metal oxides other than cerium oxide.
[0020] [Scheme 6] According to any one of schemes 1 to 5, the exhaust gas purification catalyst device, wherein the average pore diameter of the zeolite constituting the zeolite particles is the following.
[0021] [Scheme 7] According to any one of schemes 1 to 6, the exhaust purification catalyst device, wherein the zeolite constituting the zeolite particles contains one or more zeolites selected from the group consisting of MFI type, BEA type, MOR type and FER type.
[0022] [Scheme 8] According to any one of schemes 1 to 7, the exhaust purification catalyst device, wherein the silicon oxide / aluminum oxide ratio SAR of the zeolite constituting the zeolite particles is 25 or less.
[0023] [Scheme 9] The exhaust gas purification catalyst device according to any one of schemes 1 to 8, wherein the particle size d of the zeolite particles is ZEO It is not less than 4 μm and not more than 30 μm.
[0024] [Scheme 10] According to any one of schemes 1 to 9, the exhaust gas purification catalyst device, the mass M of the zeolite particles in the catalyst coating layer ZEO The mass M of the inorganic oxide particles other than the zeolite particles OX Ratio M ZEO / M OX It is 0.125 or more and 8.00 or less.
[0025] <<Scheme 11>> The exhaust gas purification catalyst device according to any one of schemes 1 to 10, which is used as a cold start catalyst.
[0026] According to the present invention, there is provided an exhaust gas purification catalyst device which can effectively adsorb and release NOx even when HC is contained together with NOx in the inflowing exhaust gas, and which has a large adsorption amount of NOx and HC, particularly NOx. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a graph showing the temporal change (time-dependent change) of NO concentration in the exhaust gas in the adsorption stage for the samples of Example 4 and Comparative Example 1 and the blank sample. DETAILED DESCRIPTION
[0028] 《Exhaust purification catalytic device》
[0029] The exhaust gas purification catalyst device of the present invention,
[0030] A substrate and a catalyst coating layer on the substrate are provided.
[0031] The catalyst coating layer includes zeolite particles, inorganic oxide particles other than the zeolite particles, and a catalyst noble metal, and
[0032] The average particle size of the zeolite particles is ZEO The average particle size d of the inorganic oxide particles other than the zeolite particles OX The ratio d ZEO / d OX Below 3.0.
[0033] The present inventors have studied the reason why the conventional exhaust gas purification catalyst device does not necessarily fully exhibit the functions of adsorbing, retaining and releasing NOx and HC, especially NOx, even when a significant amount of zeolite particles is contained in the catalyst coating layer.
[0034] Furthermore, based on the assumption that the exhaust gas flow path is not sufficiently formed in the catalyst coating layer and the NOx adsorption amount is low when the contact efficiency between the zeolite particles and the exhaust gas is poor, the structure of the catalyst coating layer in which the exhaust gas flow path is sufficiently formed was studied.
[0035] As a result, it has been successfully achieved that a sufficient exhaust gas flow path is formed in the catalyst coating layer of the exhaust gas purification catalyst device by including zeolite particles and inorganic oxide particles other than zeolite particles and adjusting the particle sizes of both.
[0036] That is, according to the mathematical sphere packing theory, when two kinds of particles with different particle sizes are filled in a space, the particle size d of the larger particle size is big The particle size d of small particles small The ratio d big / d small If the value of is sufficiently large, the small-diameter particles can be accommodated between the grids of the large-diameter particles regardless of how the large-diameter particles are filled.
[0037] However, if the big / d small If the ratio is less than 3.43654, the packing arrangement of large-size particles for accommodating small-size particles between the grids is limited, and the contact points between large-size particles decrease. As a result, an exhaust gas flow path is formed in the catalyst coating layer. big / d small If it is less than 2.41423, the lattices for large-diameter particles need to be expanded in order to accommodate small-diameter particles between the lattices, so the exhaust gas flow path in the catalyst coating layer is expanded.
[0038] In the present invention, from such a viewpoint, the average particle size d of the zeolite particles is ZEO The average particle size d of the inorganic oxide particles other than the zeolite particles OX The ratio d ZEO / d OX It is 3.4 or less, and may be 3.2 or less, 3.0 or less, 2.8 or less, 2.6 or less, 2.4 or less, 2.2 or less, or 2.0 or less.
[0039] The above consideration is applicable even when the size relationship between the zeolite particles and the inorganic oxide particles other than the zeolite particles is opposite, so d ZEO / d OXThe ratio may be 0.30 or more, 0.40 or more, 0.50 or more, 0.60 or more, 0.70 or more, 0.80 or more, 0.90 or more, or 1.00 or more.
[0040] Inorganic oxide particles other than zeolite particles, such as alumina particles, generally have a wide particle size distribution and many small particles with a particle size smaller than the average particle size are present in significant amounts. In particular, the larger the average particle size, the higher the proportion of small particles present. If the gaps between particles in the catalyst coating layer are filled with such small particles, the exhaust gas flow path in the catalyst coating layer may become insufficient. In order to avoid this, it is considered to use particles with a small average particle size as inorganic oxide particles other than zeolite particles.
[0041] From this point of view, the average particle size d of the zeolite particles is ZEO The average particle size d of the inorganic oxide particles other than the zeolite particles OX The ratio d ZEO / d OX It may exceed 1.00, be 1.05 or more, 1.10 or more, or 1.15 or more.
[0042] The average particle size of the zeolite particles and inorganic oxide particles other than the zeolite particles in this specification refers to the median diameter (D50) measured by the laser diffraction / scattering method. The measurement of the median diameter (D50) obtained by the laser diffraction / scattering method is carried out, for example, using a laser diffraction / scattering particle size distribution (particle size distribution) measuring device manufactured by Horiba, Ltd., model name "LA960" or the like.
[0043] Hereinafter, each element constituting the exhaust gas purification catalyst device of the present invention will be described in sequence.
[0044] <Zeolite particles>
[0045] The average pore size of the zeolite particles in the present invention can be The average pore size of the zeolite particles is The following results show that the NOx adsorption amount can be increased even in the presence of HC. This is considered to be due to the average pore size of the zeolite particles being When the pore size is below 1000, HC is not easy to penetrate into the pores, and NOx is preferentially adsorbed inside the pores. The average pore size of zeolite particles can be the following, the following, Below or the following.
[0046] On the other hand, in order to adsorb NOx in the pores, the average pore size of the zeolite particles preferably has a diameter that allows NOx to easily penetrate. From this viewpoint, the average pore size of the zeolite particles can be, for example, above, above, above, Above or above.
[0047] The average pore size of zeolite is measured by a gas adsorption method in accordance with JIS Z8831-3: 2010. As the adsorbed gas, for example, argon, hydrogen, nitrogen, etc. can be used.
[0048] The zeolite having the above average pore diameter may be, for example, one or more zeolites selected from the group consisting of MFI type, BEA type, MOR type, CHA type, and FER type.
[0049] The zeolite constituting the zeolite particles of the present invention may have a silicon oxide / aluminum oxide ratio SAR of 25 or less. When the SAR of the zeolite is 25 or less, it becomes an acidic zeolite with a large amount of proton acid. When a catalytic noble metal, such as Pd, is supported on such an acidic zeolite, it is easy to become a highly oxidized state, and poisoning by HC is suppressed. As a result, the advantage that the catalytic noble metal can function as a NOx adsorption site even under gas conditions where HC and NOx coexist can be obtained.
[0050] From this viewpoint, the SAR of the zeolite is 25 or less, and may be 23 or less, 20 or less, 18 or less, 15 or less, 12 or less, 10 or less, or 8 or less. On the other hand, if the SAR of the zeolite is too low, the specific surface area of the zeolite decreases, and the unfavorable situation of reducing the NOx adsorption points may occur. From the viewpoint of avoiding such a situation, the SAR of the zeolite may be 4 or more, 5 or more, 6 or more, or 7 or more.
[0051] If the particle size of the zeolite particles is ZEO If the particle size is too small, the gaps between the zeolite particles in the catalyst coating layer become narrow, and the contact between the zeolite particles and the exhaust gas may become insufficient. To avoid this, the particle size of the zeolite particles may be 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more. On the other hand, if the particle size d ZEO If the diameter is too large, the catalyst coating layer containing the zeolite particles becomes thick, which may hinder the exhaust gas flow in the exhaust gas purification catalyst device. In order to avoid this, the particle size of the zeolite particles can be 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, or 8 μm or less.
[0052] From the viewpoint of maintaining the NOx adsorption sites as much as possible, the zeolite particles preferably have fewer surface defects. From this viewpoint, the zeolite particles of the present invention preferably do not undergo a grinding step after synthesis (after crystal growth).
[0053] <Inorganic oxide particles other than zeolite particles>
[0054] The inorganic oxide particles other than the zeolite particles in the present invention may be particles containing one or more selected from aluminum oxide, silicon oxide, titanium oxide, cerium oxide, zirconium oxide, and rare earth metal oxides other than cerium oxide. The rare earth metal oxides other than cerium oxide may be oxides of metals such as yttrium, lanthanum, praseodymium, and neodymium.
[0055] Particle size d of inorganic oxide particles other than zeolite particles OX As long as the particle size d of the zeolite particles ZEO Satisfying the ratio d specified in the present invention ZEO / d OX However, from the perspective of ensuring the gaps between particles and avoiding excessive thickness of the catalyst coating layer, the particle size d OX On the other hand, if the particle size d of the zeolite particles is ZEO If the diameter is too large, the catalyst coating layer containing the zeolite particles becomes thick, which may hinder the exhaust gas flow in the exhaust gas purification catalyst device. In order to avoid this, the particle size of the zeolite particles can be 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less.
[0056] <Mass Ratio of Zeolite Particles to Inorganic Oxide Particles Other Than Zeolite Particles>
[0057] The mass M of the zeolite particles in the catalyst coating layer ZEO The mass M of the inorganic oxide particles other than the zeolite particles OX Ratio M ZEO / M OX It may be 0.125 or more or 1.00 or more, and may be 8.00 or less or 3.00 or less.
[0058] <Catalyst precious metals>
[0059] In the present invention, the catalyst noble metal is intended to function as a catalyst for adsorbing NOx (e.g., NO). Therefore, the catalyst noble metal in the present invention can be selected from platinum group elements, and in particular, can be one, two, or three selected from Pt, Pd, and Rh, and Pd is particularly preferred.
[0060] In the present invention, the catalyst noble metal can be supported on one or two particles selected from zeolite particles and inorganic oxide particles other than zeolite particles, and can be supported on zeolite particles in particular. In the exhaust gas purification catalyst device of the present invention, the catalyst noble metal is supported on the zeolite particles, so that HC poisoning of the catalyst noble metal can be suppressed, and the advantage of being able to selectively adsorb NOx on the catalyst noble metal even under gas conditions where HC and NOx coexist can be obtained.
[0061] The particle diameter of the catalytic noble metal in the present invention is arbitrary, and may be, for example, 0.1 nm or more and 20 nm or less.
[0062] The loading amount of the catalytic noble metal in the present invention can be, for example, 0.1 mass % or more, 0.2 mass % or more, 0.3 mass % or more, 0.4 mass % or more, or 0.5 mass % or more, and can be 5.0 mass % or less, 4.0 mass % or less, 3.0 mass % or less, 2.0 mass % or less, or 1.0 mass % or less, based on the mass of the zeolite particles.
[0063] <Optional Components of Catalyst Coating Layer>
[0064] As described above, the catalyst coating layer in the exhaust gas purification catalyst device of the present invention contains zeolite particles, inorganic oxide particles other than zeolite particles, and a catalytic noble metal, and may contain other optional components as necessary.
[0065] Examples of the optional components of the catalyst coating layer include a binder, an alkali metal compound, and an alkaline earth metal compound.
[0066] The binder may be, for example, alumina sol, zirconia sol, silica sol, titania sol, or the like.
[0067] The alkali metal compound and the alkaline earth metal compound are sulfates, nitrates, hydrochlorides of the desired metals, respectively, or oxides thereof.
[0068] 《Method for manufacturing exhaust gas purification catalyst device》
[0069] The exhaust gas purification catalyst device of the present invention may be manufactured by any method as long as it has the above-mentioned structure.
[0070] However, the exhaust gas purification catalyst device of the present invention can be manufactured by, for example, a method including the following steps:
[0071] (1) preparing a slurry for forming a catalyst coating layer (step 1);
[0072] (2) coating the catalyst coating layer-forming slurry on a substrate to form a coating film (step 2); and
[0073] (3) The obtained coating film is fired to form a catalyst coating layer on the substrate (step 3).
[0074] Step 1 may include, for example, the following steps.
[0075] (i) preparing a slurry containing catalytic noble metal-supported zeolite particles (step 1);
[0076] (ii) preparing a slurry containing inorganic oxide particles other than zeolite particles (step 2); and
[0077] (iii) A slurry containing catalytic noble metal-supported zeolite particles and a slurry containing inorganic oxide particles other than zeolite particles are mixed to prepare a slurry for forming a catalyst coating layer (step 3).
[0078] In step 1 of process 1, a slurry containing catalytic noble metal-supported zeolite particles is prepared. This step can be performed, for example, by placing particles consisting of the desired zeolite and a precursor of the desired catalytic noble metal into a solvent, such as water, wet-grinding them using an appropriate pulverizing means, and classifying them as needed.
[0079] The precursor of the catalytic noble metal may be, for example, sulfate, nitrate, hydrochloride, complex, etc. of the desired catalytic noble metal. In order to uniformly disperse the catalytic noble metal on the zeolite particles, the precursor of the catalytic noble metal is preferably soluble in a solvent.
[0080] In step 2 of process 1, a slurry containing inorganic oxide particles other than zeolite particles is prepared. This step can be performed, for example, by placing the desired inorganic oxide particles into a solvent such as water, wet-grinding them using an appropriate pulverizing means, and classifying them as needed.
[0081] Step 1 and step 2 of process 1 may be performed in different orders.
[0082] Then, in step 3 of process 1, a slurry containing catalytic noble metal-supporting zeolite particles and a slurry containing inorganic oxide particles other than zeolite particles are mixed at a predetermined ratio to prepare a slurry for forming a catalyst coating layer.
[0083] In step 2, the catalyst coating layer-forming slurry is applied onto the substrate to form a coating film. The slurry can be applied by a known method or by a method in which a person skilled in the art appropriately modifies a known method.
[0084] Then, in step 3, the obtained coating film is fired to form a catalyst coating layer on the substrate, thereby obtaining the exhaust gas purification catalyst device of the present invention. After coating and before firing, the coating film may be dried as necessary.
[0085] The drying and calcining of the coating film can be performed by a known method or by a method in which a person skilled in the art appropriately modifies the known method.
[0086] <Purpose of the exhaust gas purification catalyst device>
[0087] The exhaust gas purification catalyst device of the present invention has the function of effectively adsorbing NOx and HC, especially NOx, at low temperature and holding it until high temperature, and releasing NOx and HC, especially NOx, at high temperature.
[0088] Therefore, the exhaust gas purification catalyst device of the present invention can be used as a cold start catalyst.
[0089] The exhaust gas purification catalyst device of the present invention as a cold start catalyst can be applied to, for example, an exhaust gas purification catalyst system combined with a known three-way catalyst. The exhaust gas purification catalyst system can have a structure in which the exhaust gas purification catalyst device of the present invention is arranged on the upstream side of the exhaust path and a known three-way catalyst is arranged on the downstream side.
[0090] Example
[0091] 《Example 1》
[0092] 1. Preparation of Pd / zeolite particle slurry
[0093] 100 parts by mass of commercially available MFI zeolite (SAR23, average pore size ) and palladium nitrate equivalent to 0.5 mass % in terms of Pd metal relative to the zeolite were added into pure water, and ground using a ball mill filled with alumina balls as a grinding medium, thereby preparing a zeolite having an average particle size (D50 particle size) d ZEO The slurry is a Pd / zeolite particle slurry containing zeolite particles of 5.7 μm.
[0094] 2. Preparation of slurry containing alumina particles
[0095] Alumina was put into pure water and ground using a ball mill filled with alumina balls as a grinding medium to prepare a particle size containing an average particle size (D50 particle size) of d ZEO The slurry contains alumina particles having a size of 31.0 μm.
[0096] 3. Preparation of slurry for forming catalyst coating layer
[0097] The Pd / zeolite particle-containing slurry and the alumina particle-containing slurry were mixed so that the mass ratio of Pd / zeolite:alumina was 1:4, thereby preparing a slurry for forming a catalyst coating layer.
[0098] 4. Preparation of evaluation samples
[0099] The catalyst coating layer forming slurry was poured into a cordierite straight honeycomb substrate test piece having a capacity of 0.035 L, and unnecessary slurry was blown off and removed with a blower, thereby forming a coating film of the catalyst coating layer forming slurry on the wall surface of the test piece.
[0100] The obtained coating film was dried at 120°C for 2 hours and then calcined at 500°C for 2 hours to form a catalyst coating layer, thereby preparing an evaluation sample. The coating amount of the catalyst coating layer in the evaluation sample was 80 g / L (Pd / zeolite particles 16 g / L, alumina particles 64 g / L), and the Pd amount was 0.08 g / L (Pd loading in Pd / zeolite particles 0.5 mass %).
[0101] The particle size d of the Pd / zeolite particles contained in the catalyst coating layer of the evaluation sample is ZEO The particle size of alumina particles AlO The ratio d ZEO / d AlO is 0.18.
[0102] 5. Evaluation of NO adsorption
[0103] The evaluation samples obtained above were subjected to a three-stage treatment consisting of a pretreatment stage, an adsorption stage, and a desorption stage. In each stage, sample gas was supplied to the evaluation samples under the conditions shown in Table 1, and the change in NO concentration in the exhaust gas during the adsorption stage over time was investigated. The desorption stage included two steps: maintaining at 100°C for 180 seconds, and then increasing the temperature at 20°C / min for 1,350 seconds (reaching a temperature of 550°C).
[0104] Table 1
[0105]
[0106] Furthermore, the same three-step treatment was performed using a honeycomb substrate without a catalyst coating layer as a blank sample, and the change in NO concentration in the exhaust gas with time in the adsorption step was examined.
[0107] Then, the difference between the NO concentration in the exhaust gas of the blank sample and the NO concentration in the exhaust gas of the evaluation sample was integrated by the time required for the adsorption phase, and the obtained value was converted into the NO amount in mg (milligrams), thereby calculating the NO adsorption amount of the catalyst coating layer.
[0108] In Table 1, the C3H6 concentration in the adsorption stage is "600ppm-C1", which means that the C3H6 concentration is 600ppm in terms of methane. Therefore, in this case, the concentration of C3H6 molecules is 200ppm.
[0109] The amount of NO adsorbed by the catalyst coating layer in the evaluation sample of Example 1 was 26.1 mg.
[0110] 《Examples 2 to 4 and Comparative Example 1》
[0111] 2. Preparation of slurry containing alumina particles
[0112] The average particle size d of the alumina particles contained in the alumina particle slurry is AlO The samples for evaluation were prepared in the same manner as in Example 1 except that the above were adjusted as shown in Table 2, and the NO adsorption amount was evaluated. The evaluation results are shown in Table 2.
[0113] in addition, Figure 1 A graph showing the time-dependent changes in NO concentration in exhaust gas during the adsorption phase for the samples of Example 4 and Comparative Example 1, and a blank sample. Figure 1 The numerical value of the horizontal axis "elapsed time (seconds)" of the coordinate graph represents the cumulative time from the start time of the preprocessing stage.
[0114] Table 2
[0115]
[0116] From the results in Table 2, it can be confirmed that the particle size d of the Pd / zeolite particles is ZEO The particle size of alumina particles AlO The ratio d ZEO / d AlO The samples of Examples 1 to 4 with a value of less than 3, and the ratio d ZEO / d AlO Compared with Comparative Example 1, which is more than 3, the amount of NO adsorption is significantly greater. ZEO / d AlO The samples of Examples 2 to 4 having a value of 0.3 or more had particularly large amounts of NO adsorption.
[0117] Furthermore, it should be noted that the NO adsorption amounts shown in Table 2 are values measured using a sample gas containing C3H6 together with NO.
Claims
1. An exhaust gas purification catalyst device comprising a substrate and a catalyst coating layer on the substrate, The catalyst coating layer includes zeolite particles, inorganic oxide particles other than the zeolite particles, and a catalytic noble metal. The average particle size of the zeolite particles is ZEO 5.7μm or less, The average particle size of the zeolite particles is ZEO The average particle size d of the inorganic oxide particles other than the zeolite particles OX The ratio of d ZEO / d OX More than 1.00 and less than 2.85, and The catalytic noble metal is supported on the zeolite particles. 2 . The exhaust gas purification catalyst device according to claim 1 , wherein the catalyst noble metal is one or two selected from Pt and Pd.
3. The exhaust gas purification catalyst device according to claim 1 or 2, wherein the inorganic oxide particles other than the zeolite particles are particles containing one or more selected from the group consisting of aluminum oxide, silicon oxide, titanium oxide, ceria and zirconium oxide, and rare earth metal oxides other than ceria.
4. The exhaust gas purification catalyst device according to any one of claims 1 to 3, wherein the average pore size of the zeolite constituting the zeolite particles is the following. 5 . The exhaust gas purification catalyst device according to claim 1 , wherein the zeolite constituting the zeolite particles contains one or more zeolites selected from the group consisting of MFI type, BEA type, MOR type and FER type. 6 . The exhaust gas purification catalyst device according to any one of claims 1 to 5 , wherein a silica / alumina ratio SAR of zeolite constituting the zeolite particles is 25 or less.
7. The exhaust gas purification catalyst device according to any one of claims 1 to 6, wherein the particle size d of the zeolite particles is ZEO It is not less than 4 μm and not more than 5.7 μm.
8. The exhaust gas purification catalyst device according to any one of claims 1 to 7, wherein the mass M of the zeolite particles in the catalyst coating layer is ZEO The mass M of the inorganic oxide particles other than the zeolite particles OX Ratio M ZEO / M OX It is 0.125 or more and 8.00 or less.
9. The exhaust gas purification catalyst device according to any one of claims 1 to 8, which is used as a cold start catalyst.
Citation Information
Patent Citations
Catalyst for exhaust gas purification and production method therefor
JP2006035130A
Purifying catalyst for gas within reflow furnace, method for preventing contamination of reflow furnace, and reflow furnace
CN101522305A
Platinum oxidation catalyst and method for purifying exhaust gas using same
CN104582843A
Exhaust gas purifying catalyst having excellent silicon tolerance
CN104884164A
Catalyst for controlling exhaust emission
JP1989139144A